The Norton introduction to literature - Mays, Kelly J. (W.W. Norton & Company, 2016)
New to the tweflth edition: Fifty-one selections: There are nine stories, forty new poems, and two new plays on this Tweflth edition of the Nortom Introduction to Literature.